Winter wheat growing in Ukraine: ecological assessment of technologies by the influence on soil fertility - Lera BONDAR; Nataliia MAKARENKO (Acta Agriculturae Slovenica)
Modern technologies of winter wheat growing need to be improved taking into account the results of ecological evaluation of their impact on soil fertility indices. We aimed to assess the technologies of winter wheat growing in different soil and climatic conditions of Ukraine by their influence on soil fertility. It is known that in order to estimate ecological safety of crop growing technologies, it is advisable to use a method based on identifying negative impacts on soil fertility. We propose the group of deviation values from the optimum as follows: (i) strong, which leads to an unsatisfactory ecological condition (˃ 50 %), (ii) average that provides a satisfactory state (˃ 25 %, but ˂ 50 %), (iii) moderate, which provides a normal state (≤ 10 %, but ˂ 25 %), (iv) absent, an optimal condition is provided (˂ 10 %). It is revealed that technologies of winter wheat growing in the conditions of Polissya, Forest-steppe and Steppe Zones of Ukraine can have a negative influence on potassium regime in soils, the influence by intensity can vary from moderate to strong. In Polissya and Forest-steppe, winter wheat growing can lead to deterioration of soil pH status. In Steppe, along with the potassium regime, the technologies can negatively influence soil nitrogen status and the effect may be characterized as strong.